Exchange broadening of EPR line in ZnO:Co - Sati, P.; Pashchenko, V.; Stepanov, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We study the X-band EPR spectra of Co2+ in single crystalline Zn1-xCoxO (x = 0.001–0.075) thin films grown by plasma-assisted molecular beam epitaxy. By analyzing the EPR linewidth behavior we argue that the exchange-narrowing model, usually applied to Mn-based II-VI DMS, fails here and that a combined effect of exchange and dipolar broadening can explain the linewidth variation with Co content and temperature.